2019
DOI: 10.3390/ijerph16091532
|View full text |Cite
|
Sign up to set email alerts
|

Helicopter Emergency Medical Service (HEMS) Response in Rural Areas in Poland: Retrospective Study

Abstract: The aim of the study was to identify the characteristics of missions performed by HEMS (Helicopter Emergency Medical Service) crews and the analysis of health problems, which are the most common cause of intervention in rural areas in Poland. The study was conducted using a retrospective analysis based on the medical records of patients provided by the HEMS crew, who were present for the emergencies in rural areas in the period from January 2011 to December 2018. The final analysis included 37,085 cases of int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 44 publications
3
12
0
Order By: Relevance
“…More than one third of HEMS missions resulted in at least one critical care intervention, particularly endo-tracheal intubation and ultrasound examination. This proportion of interventions has also been reported in other HEMS studies, although the definitions of a critical care intervention varied [17, 18]. Although the physicians did not specify what kind of ultrasound examination they performed (eFAST, FATE), the examination was included in this study as a critical care intervention as it may distinguish between, or rule out, specific emergency conditions such as ruptured aortic aneurysm, acute cardiac failure and pulmonary diseases, impacting both on scene treatment and decision-making in triage and escort [19, 20].…”
Section: Discussionsupporting
confidence: 71%
“…More than one third of HEMS missions resulted in at least one critical care intervention, particularly endo-tracheal intubation and ultrasound examination. This proportion of interventions has also been reported in other HEMS studies, although the definitions of a critical care intervention varied [17, 18]. Although the physicians did not specify what kind of ultrasound examination they performed (eFAST, FATE), the examination was included in this study as a critical care intervention as it may distinguish between, or rule out, specific emergency conditions such as ruptured aortic aneurysm, acute cardiac failure and pulmonary diseases, impacting both on scene treatment and decision-making in triage and escort [19, 20].…”
Section: Discussionsupporting
confidence: 71%
“…A similar analysis was performed in the current study. compared HEMS missions carried out in Poland and demonstrated that HEMS teams were dispatched most often in the period May-August [37]. Another study by included an analysis of HEMS missions in rural areas over an 8-year period, and found that most such HEMS missions in rural areas occurred in the summer [38].…”
Section: Discussionmentioning
confidence: 99%
“…Strehlow et al (2016) also reported that EMS team members almost always measured the pregnant patients' heart rate and blood pressure, and placed them in the left lateral position [31]. found that HEMS missions in rural areas more often involved mechanical ventilation, patient immobilization, intravenous cannulation, chest compressions, and endotracheal intubation [37]. In the current study, EMS interventions in rural areas for pregnant patients with vaginal bleeding most commonly included the following procedures: blood pressure measurement, monitoring of vital parameters, intravenous cannulation, and blood glucose measurement.…”
Section: Discussionmentioning
confidence: 99%
“…Certain rural and frontier locations with very limited medical resources and capabilities are hundreds or thousands of miles from advanced medical care, and air medical services may be the only practical resource to help transport these patients to a higher level of care. (114)(115)(116) Though some of these areas are accessible by roads, the transport interval between facilities using ground vehicles may be half a day or more. In these cases, fixed-wing air medical services may be used when transport distances or weather conditions are beyond the capability of HEMS.…”
Section: Accepted Manuscriptmentioning
confidence: 99%